Towards a behavioral profile of degree adverbs in Mainland and Taiwan Mandarin news language - Yan Xiao; Qiurong Zhao (PLoS ONE, 2026)
The major difference between Mainland Mandarin and Taiwan Mandarin in adverb usage lies in degree adverbs. Exploring the similarities and differences in degree adverbs across both sides of the strait not only helps reveal the subtle differences between Chinese dialectal varieties, but also helps broaden the path for computer-assisted compilation of language dictionaries, and enlighten the research method used by language variation studies, comparative language studies and other applied linguistics. This paper compares degree adverbs in Mainland Mandarin and Taiwan Mandarin based on self-built news corpus by using BP (behavior profile) approach and finds that: (1) Degree adverbs with high and medium intensification/mitigation level are more commonly used while degree adverbs with extreme and low intensification/mitigation level are avoided on both sides. In addition, Taiwan uses more extreme degree adverbs than Mainland. (2) The usage of degree adverbs in Mainland and Taiwan Mandarin is significantly related to the semantic prosody, word class, and syntactic function of the words they modify. Specifically, in terms of the semantic prosody of the words they modify, degree adverbs in Mainland modify more positive semantic prosody than those in Taiwan. In terms of the word class of the words they modify, degree adverbs in Mainland mostly modify verbs while degree adverbs in Taiwan corpus mostly modify adjectives. In terms of the syntactic function of the words they modify, degree adverbs in Mainland mostly modify predicates while degree adverbs in Taiwan mostly modify attributives. (3) Cluster diagram analysis shows that the unique degree adverbs on both sides can be substituted with degree adverbs that have similar behavioral profile by each other, which reflects the openness and flexibility of language. This article further points out that the similarities and differences between degree adverbs in Mainland and Taiwan are mainly influenced by news language norms, regional socio-cultural differences, and language change and contact. This paper aims to provide new insights for language users regarding the subtle differences between dialectal varieties in news language and beyond, thereby facilitating more effective communication and the appropriate language use.